Transfer of Navicula hochstetteri var. patagonica Frenguelli to the genus Cavinula (Cavinulaceae, Bacillariophyta) and lectotype designation - Lameiro, Rubén Agustín (2022)
We give a detailed morphological description of the original material of N. hochstetteri var. patagonica and we propose to transfer this taxon to the genus Cavinula and raise it to species level as Cavinula patagonica below. A specimen from the original material of the Joaquín Frenguelli diatom collection is here designated as lectotype.